A novel RING finger protein CqRNF152-like with self-ubiquitination activity inhibits white spot syndrome virus infection in a crustacean Cherax quadricarinatus. Issue 94 (November 2019) - Zheng, Shu-cheng; Chang, Xue-jiao; Li, Wei-dong; Wang, Hao; Guo, Li-mei; Wang, Ke-jian; Liu, Hai-peng
Abstract: Really Interesting New Gene (RING) finger proteins are highly conserved molecules that participate in a variety of biological processes such as regulation of development, apoptosis and antiviral immunity in vertebrates. However, the functions of RING finger proteins are still poorly understood in crustaceans. Previously, we found that the transcript of a homolog of RING finger protein 152 ( Cq RNF152-like) was up-regulated in a differentially expressed transcriptome library of the haematopietic tissue (Hpt) cells from red claw crayfish Cherax quadricarinatus upon white spot syndrome virus (WSSV) infection, which is one of the most devastating viral diseases for crustaceans like shrimp and crayfish. The full-length cDNA sequence of CqRNF152-like was then identified with 975 bp, including an ORF of 685 bp that encoded a 195 amino acids protein, a 5′- UTR of 180 bp, and a 3′-UTR with a poly (A) tail of 207 bp. The conserved domain prediction showed that Cq RNF152-like contained a conserved RING-finger domain. Gene expression analysis showed that CqRNF152-like was distributed in all tissues examined and the transcript is significantly up-regulated after WSSV challenge both in vivo in Hpt tissue and in vitro in cultured Hpt cells. Furthermore, the transcripts of both an immediate early gene ie1 and a late envelope protein gene vp28 of WSSV were clearly increased in the Hpt tissues, hemocytes and cultured Hpt cells after gene silencing of Cq RNF152-like, which were further proved to be significantly decreased after overloading of recombinant Cq RNF152-like protein in Hpt cell cultures. Meanwhile, Cq RNF152-like was found to bind with WSSV envelope protein VP28 by proteins pull-down assay. Similar to most of RNF proteins, Cq RNF152-like protein sequence contained a conserved RING-finger domain and showed self-ubiquitination activity in a RING finger domain dependent manner. Taken together, Cq RNF152-like is likely to function as an antiviral molecular against WSSV infection through interaction with the envelope protein VP28 in a crustacean C . quadricarinatus . This is the first report that a RING finger protein with directly antiviral functions via interaction with viral protein and self-ubiquitination activity in crustacean, which sheds new light on the molecular mechanism of WSSV infection and the control of white spot disease. Highlights: Cq RNF152-like was responsive to WSSV infection in vivo and in vitro. Cq RNF152-like inhibited WSSV replication in vivo and in vitro. Cq RNF152-like bound to WSSV envelope protein VP28. Cq RNF152-like exhibited self-ubiqutination activity in a RING domain-dependent manner.